COMMUNICATION OF MATLAB GUI AND ANSYS MAXWELL: AN EDUCATION TOOL FOR TUBULAR LINEAR GENERATOR - Arslan, S; Gürdal, O; Akkaya Oy, S (university of el oued/جامعة الوادي, 2019)
In this study, analytical calculations of a tubular linear generator model are performed by using Matlab Gui for free-piston applications. A training tool including the processes of design of linear generator, sizing with the analytical equations and analyzing with the finite elements methods was suggested. Geometric dimensions in Matlab Gui interface are solved by transferring automatically to finite element model Ansys-Maxwell 2D-rz plane. The results of analytical analysis are in concordance with the results of finite elements. In addition, Ansys-Maxwell Script and Matlab codes are given in the appendix.
Article
Keywords: Linear generator; magnetic field; ansys maxwell; matlab gui; visual basic script